Duty of Candour: The Legal and Regulatory Risk that Dentistry Forgot. Issue 4 (December 2022) - Lewis, Kevin
This article is based upon a webinar presented by the author in July 2022 as part of the ongoing collaboration between CGDent and ProDental CPD, and the handouts provided for those webinar participants. It also reflects the author's seminar given at the Dentistry Show in London in October 2022. Some of the background information also appeared in lectures on this topic given by the author to the UK Committee of Postgraduate Dental Deans and Directors (COPDEND) and East Midlands Dental School in 2015–2017. It aims to bust some myths about the duty of candour as it applies to dentistry and explains its implications for practice owners, dentists and other team members, the conversations we need to be having and the records we need to keep in order to satisfy the legal, ethical and perhaps contractual aspects of this duty, as well as the human aspects. It should be noted that the situation regarding the legal duty of candour differs across the four nations of the UK; this article explains the dynamic nature of those differences, but in terms of detail it focuses upon the situation as it exists in England where the duty has existed for much longer and affecting more members of the dental profession.